S‐g‐C3N4/N−TiO2 @PTFE Membrane for Photocatalytic Degradation of Tetracycline. Issue 40 (25th October 2022) - You, Xuehui; Liu, Fang; Jiang, Guofei; Chen, Shuhua; An, Beiya; Cui, Rongli
Abstract: Herein we synthesized S‐g‐C3 N4 and N−TiO2 catalysts by hydrothermal and calcination technologies and SCN/NT@PTFE membrane by a vacuum filtration method. The morphology and composition of the synthesized materials were analyzed by different characterization methods (SEM/HRTEM/XRD/XPS/UV‐vis et.). The effects of different catalysts, pollutant concentrations, mass of catalyst and pH on the photo‐degradation of tetracycline were investigated. The degradation rate of tetracycline by SCN/NT‐2@PTFE membrane was as high as 99.9 % after 2 h of illumination. This was mainly because heterogeneous structure between S‐g‐C3 N4 and N−TiO2 broadened the light absorption range and suppressed the carrier complex. Superoxide radicals (⋅O2 − ) were proved to play a dominant role in the degradation reaction. After 20 days of stirring in water, the photocatalytic performance of membrane decreased slightly, demonstrating its good stability. The study of SCN/NT‐2@PTFE membrane provides a new direction for the development of photocatalysis and membrane. Abstract : Degradation experiments of TC suggested that SCN/NT‐2@PTFE composites showed the best photocatalytic performance under the optimal conditions, the degradation rate of tetracycline reached 99 % after 120 min of irradiation. The preparation of SCN/NT‐2@PTFE composite membrane can solve the problem of difficult recovery and secondary contamination of powder catalysts.